The reality of the social welfare role in light of the Syrian war An exploratory study of the reality of the orphanage in Lattakia Al Masaa'i Charitable Society as a model - العقيبة, هند; اسماعيل, رندا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Social care is one of the basic matters to which societies at all levels of development attach importance and interest, especially care when it comes to the deprived and those who are unable to support themselves, and among these groups is the segment of orphan children who have lost their parents or one of them and do not have a breadwinner. The research aims to shed light on the reality of care homes in light of the Syrian war by conducting an exploratory study on the orphanage in the city of Latakiya, considering social care a duty on society and a right for individuals. The research started from several hypotheses, the most important of which are: - The Syrian war has negatively affected the social care situation. - The Syrian war has affected the number of donors and the number of orphans in the home. Results: - The study concluded that the impact of the war was evident in the increase in the number of orphaned children in the home. - Increasing the number of donors with in-kind and cash assistance for children inside the home.